Poverty Alleviation Strategy through Local Government Collaboration - Aziz Widhi Nugroho (LPPM Universitas Terbuka, 2025)
Poverty is the focus of government attention in a country. One important aspect to support the Poverty Alleviation Strategy is the availability of accurate and transparent poverty data. Data accuracy is certainly balanced with cross-sectoral collaboration between OPDs, where policies are under the authority of the relevant agencies. Wonogiri, which we know has an initial poverty rate of above 13 percent, is now approaching 1 digit. This research was conducted using a qualitative method with inductive descriptive writing to obtain data. The scope of the research contains efforts to overcome poverty through collaboration. The results of research related to poverty alleviation through collaboration with the Regional Government are influenced by various factors including low levels of community income, minimal health, limited education, access to goods and services is still difficult, location or domicile, geographic location, gender, and environmental conditions. Referring to the government's strategy in poverty alleviation, poverty can be overcome through collaboration between relevant agencies in handling it and by creating a special team that focuses on dealing with poverty. The obstacles encountered when poverty alleviation efforts stagnate in ordinary programs that emphasize the ceremonial side alone rather than on needs.